A novel material of HfScW2PO12 with negative thermal expansion from 140 K to 1469 K and intense blue photoluminescence. (January 2017) - Cheng, Yongguang; Liang, Yuan; Mao, Yanchao; Ge, Xianghong; Yuan, Baohe; Guo, Juan; chao, Mingju; Liang, Erjun
Graphical abstract: Highlights: A novel material HfScW2 PO12 with NTE and intense photoluminescence is presented. It exhibits NTE in a large temperature range covering RT without hygroscopicity. It exhibits bright blue-light emission covering the visible range. The mechanisms for the NTE and PL are presented. The integrated excellent functionalities may found important applications in w-LEDs. Abstract: A novel material of HfScW2 PO12 with negative thermal expansion (NTE) is presented. It is shown that it adopts an orthorhombic structure with space group Pnca (No. 60) and exhibits NTE with an intrinsic coefficient of thermal expansion −1.27 × 10 −6  K −1 from 140 K to 1469 K. Besides the NTE property, HfScW2 PO12 possesses intense blue photoluminescence (PL). The PL intensity and CIE chromaticity coordinates show good thermal stability in the temperature range from room temperature to 10 K. All the results indicate that HfScW2 PO12 may have a potential application as a near ultraviolet LED convertible blue emitting phosphor for white LEDs.